2023
DOI: 10.1021/jacs.3c04746
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Hybrid Copolymerization of Sulfur with Acrylate: Strategy for Synthesis of High-Performance Sulfur-Based Polymers

Abstract: Copolymerization of elemental sulfur (S8) with vinyl monomers to develop new polymer materials is significant. Here, for the first time, we report the anionic hybrid copolymerization of S8 with acrylate at 25 °C, yielding a copolymer with short polysulfide segments; i.e., each of them consists of only one to four sulfur atoms. The formation of a longer polysulfide segment would be ceaselessly disrupted by carbon anions through the chain-transfer reaction. The copolymer of S8 with diacrylate was cross-linked an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The signals in the range of 3000–3600 and 1000–1170 cm –1 were due to the vibration absorption signals of −OH/–NH 2 groups and the stretching vibration signals of −C–O– bonds in PBEHA, respectively . The signals in the ranges of 980–1000, 860–920, and 770–840 cm –1 corresponded to in-plane B–N, B–O–C, and N–B–N bonds. ,,, These signals cannot be found for PEHA. No CC bond (1610 cm –1 ) or plane B–O–H bending (1190 cm –1 ) signals were observed for all copolymers, illustrating high comonomer conversions.…”
Section: Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The signals in the range of 3000–3600 and 1000–1170 cm –1 were due to the vibration absorption signals of −OH/–NH 2 groups and the stretching vibration signals of −C–O– bonds in PBEHA, respectively . The signals in the ranges of 980–1000, 860–920, and 770–840 cm –1 corresponded to in-plane B–N, B–O–C, and N–B–N bonds. ,,, These signals cannot be found for PEHA. No CC bond (1610 cm –1 ) or plane B–O–H bending (1190 cm –1 ) signals were observed for all copolymers, illustrating high comonomer conversions.…”
Section: Results and Discussionmentioning
confidence: 92%
“…RTP vitrimers were readily synthesized via one-step multicomponent hybrid copolymerization, 6-hexanediamine (HDA), ethylene glycol diglycidyl ether (EGDE), AM, and BA. , During the copolymerization, the reaction between HDA and EGDE has been widely studied for the preparation of epoxide resin (Figure A) . AM was incorporated into the copolymer system via the aze-Michael addition with HDA as well as the oxa-Michael addition reaction with the negative oxygen-ion formed by the ring opening reaction of EGDE .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Very recently, anionic inverse vulcanization of diacrylate has been developed for the easy synthesis of cross-linked polysulfides. [22,28] Additionally, elemental sulfur can react with acrylamides to produce small molecular polysulfides in the presence of an organobase. [29] It is important to note that such anionic step-growth reactions with sulfur have so far been limited to electron-deficient alkenes.…”
Section: Step-growth Polymerization Of Aziridines With Elemental Sulfurmentioning
confidence: 99%
“…[21] Another notable advancement was made by Zhang et al, who reported an anionic hybrid copolymerization of sulfur with diacrylate at 25 °C, yielding a copolymer with short polysulfide segments. [22] Despite the significant progress that has been achieved, exploring non-vinyl copolymers remains a big challenge, as does the direct transformation of elemental sulfur into polysulfides with a controlled linear structure.…”
Section: Introductionmentioning
confidence: 99%
“…Inverse vulcanization reported by Pyun and coworkers is a facile and powerful methodology to convert the abundant byproduct sulfur from petroleum industry into sulfur-rich polymers. In addition to petrobased feedstocks, biobased monomers have also been utilized to prepare inverse vulcanized polymers. Owing to the unique chemophysical properties arising from the high sulfur content, these materials show great potential for various applications, including the refractive index, Li–S battery cathodes, , self-healing materials, , heavy metal capture, , infrared imaging, and also injecting new vitality into rubber composites. Guo et al reported that the sulfur and styrene copolymers through inverse vulcanization as an efficient vulcanizing agent could cross-link diene rubbers in a green manner .…”
Section: Introductionmentioning
confidence: 99%